2018
DOI: 10.1093/ijnp/pyy023
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Synapsin I and II upon Treatment by Lithium and Valproic Acid in Various Brain Regions

Abstract: IntroductionDue to the heterogeneity of psychiatric illnesses and overlapping mechanisms, patients with psychosis are differentially responsive to pharmaceutical drugs. In addition to having therapeutic effects for schizophrenia and bipolar disorder, antipsychotics and mood stabilizers have many clinical applications and are used unconventionally due to their direct and indirect effects on neurotransmitters. Synapsins, a family of neuronal phosphoproteins, play a key regulatory role in neurotransmitter release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…reached plasma lithium levels of: 1.07±0.039 mmol/L after treatment, concentrations similar to those reached in patients under lithium therapy [30,52]. Lithium-treated Ank3 p.W1989R mice showed higher spontaneous inhibitory postsynaptic current (sIPSC) frequency compared to vehicletreated Ank3 p.W1989R mice (Fig.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…reached plasma lithium levels of: 1.07±0.039 mmol/L after treatment, concentrations similar to those reached in patients under lithium therapy [30,52]. Lithium-treated Ank3 p.W1989R mice showed higher spontaneous inhibitory postsynaptic current (sIPSC) frequency compared to vehicletreated Ank3 p.W1989R mice (Fig.…”
Section: Introductionsupporting
confidence: 69%
“…To explore if lithium treatment modifies inhibitory neurotransmission in Ank3 p.W1989R mice, we performed whole-cell patch-clamp recordings in pyramidal neurons in WT, Ank3 p.W1989R, and Ank3 p.W1989R mice treated with lithium for 19-21 days. Ank3 p.W1989R littermates given lithium reached plasma lithium levels of: 1.07±0.039 mmol/L after treatment, concentrations similar to those reached in patients under lithium therapy [30,52]. Lithium-treated Ank3 p.W1989R mice showed higher spontaneous inhibitory postsynaptic current (sIPSC) frequency compared to vehicle-treated Ank3 p.W1989R mice (Fig.…”
Section: Resultsmentioning
confidence: 60%
“…Studies on the effects of chronic Li exposure on SYN reported no effect on either protein 40,41 or mRNA levels 49 . On the other hand, Li exposure was shown to increase mRNA levels of Synapsins, a class of proteins that like SV2A and SYN is located on presynaptic vesicles and is involved in neurotransmitter release 22 , and is reduced in BD 40 . The latter study, however, did not see an effect of Li on Synapsin protein levels in the hippocampus.…”
Section: Summary and Interpretation Of Resultsmentioning
confidence: 99%
“…In this context, several studies investigating the effect of antipsychotic and mood-stabilising medication on the animal brain provide evidence to suggest that synaptic changes may occur upon administration of these drugs. These include altered spine density 20 , dendritic branching 21 , and altered expression of synaptic protein markers such as Synapsin, SNAP-25, Synaptophysin, and PSD-95 [22][23][24] , however SV2A was not assessed in these studies. In earlier work we demonstrated contrasting effects of the antipsychotic drugs Haloperidol (HAL) and…”
Section: Introductionmentioning
confidence: 99%
“…Although the genes encoding the presynaptic proteins have been studied in relation to different neurodevelopmental/psychiatric disorders, including ASD, the expression of the key proteins responsible for synapse formation, maintenance of their proper structure, and neurotransmitter release was not investigated. So far, the single nucleotide polymorphisms and mutations in the genes coding synaptic proteins have been examined [3,13,[20][21][22][23][43][44][45][46]. This suggests that the synapse is a possible site of autism origin.…”
Section: Discussionmentioning
confidence: 99%